The Effect Of Training And Human Resource Development On The Performance Of Office Employees In Desadi, South Bengkulu Regency, Bengkulu Province - Ahmad Lubis; Karona Cahya Susena; M Rahman Febliansa (UNIVED Press, 2026)
This research confirms that training and development of human resources (HR) for village officials has a positive and significant effect on the performance of village office employees. Systematic and continuous training is very important to increase the knowledge, skills and professionalism of village officials, so that they can overcome the problems of late reporting, low understanding of regulations and limited use of technology. Human resource development that focuses on capacity, leadership and digital competency increases the effectiveness of public services and supports optimal village development. Training has a more dominant influence in increasing this performance. This research aims to analyze the influence of training and development of human resources (HR) on the performance of village office employees in South Bengkulu Regency. The research uses a quantitative approach with data obtained through questionnaires, interviews, observation and documentation. Independent variables include training (X1) and HR development (X2), while the dependent variable is employee performance (Y). Data analysis was carried out using multiple linear regression, t test, F test, and coefficient of determination (R²). The research results show that HR training and development has a positive and significant effect on employee performance, both partially and simultaneously. The regression coefficient value for training is 0.357 and human resource development is 0.183, with an F_count value of 15.297 which is greater than F_table 3.092 at a significance level of 5%. The determination value (R²) of 0.246 indicates that 24.6% of the variation in employee performance is influenced by HR training and development. These findings confirm that improving the quality of training and human resource development in a directed and sustainable manner can increase employee professionalism, motivation and productivity in supporting public services and village development.